The Effectiveness of Transdiagnostic Therapy on Anxiety, Depression, Cognitive Strategies of Emotional Regulation, and General Performance in Women with Comorbid Anxiety and Depression - Farzaneh Hooman; Mahnaz Mehrabizadeh Honarmand; Yadolah Zargar; Iran Davodi (Fasa University of Medical Sciences, 2015)
Background & Objectives: The purpose of the current study was investigation the effectiveness of group transdiagnostic therapy on anxiety, depression, cognitive strategies of emotional regulation, and general performance in women with comorbid anxiety and depression in Ahwaz, Iran. Materials & Methods: The population of this study was all women patients who referred to the Health Services Center of Ahwaz Oil Industry, (from December 2013 to May 2014). The sample consisted of 45 patients with comorbid anxiety and depression who were selected by simple, random sampling method and were assigned to experimental, placebo, and control groups. Prior to the intervention, the questionnaire was completed by all three groups. The experimental group received eight sessions of group therapy. The control group received no intervention, and placebo group, like the experimental group, only attended the eight sessions. Results: The results of MANCOVA and Benferoni post hoc showed that in the experimental group, anxiety, depression, and negative cognitive strategies of emotional regulation decreased and positive cognitive strategies of emotional regulation increased, compared with the placebo and the control groups.  In addition, a significant improvement was achieved in the general performance of the experimental group; however, no noticeable differences were found between the placebo and the control groups in terms of the variables. Conclusion: Group transdiagnostic therapy is effective in reducing symptoms of anxiety and depression and improving emotional regulation.